Erratum to “Pleistocene volcanism along the margins of the Canal de Ballenas transform fault, Gulf of California” - Arturo Martín-Barajas; Axel K. Schmitt; Bodo Weber; Margarita López-Martínez (Revista Mexicana de Ciencias Geológicas)
In the above article, the data of the reference: